An Overview of Latin American Health Policies and Debates - Asa Cristina Laurell (Social Medicine Publication Group, 2024)
It is now 15 years since the publication of Investing in Health (World Bank, 1993), a report which set the course for health care system reform in Latin America and around of the world. Since that time a great many studies about the reforms have been published and new reforms have been launched to "correct" the defects of the earlier ones. The objective of this paper is to call into question the entire current political debate over health care, as well as to clarify key concepts and practices. To this end I will analyze the current vogue of interrelated proposals for a second reform of the state. I will examine debates over insurance as a way of grant universal coverage; the separation between the regulation, financing and provision of health services; and the public private partnerships for the construction, financing, and management of hospitals. This paper will also examine the development of a new scientific discourse around "evidence-based policies" and academic referral networks. The goal of this paper is not to offer a comprehensive treatment of these issues, but rather to question some assumptions and contribute to the larger debate.